Odpowiedź :
4 * (5y +1) * (1 - 5y) -5 * (4x + 1) * (1 - 4x) =
4* ( 5*0,1 + 1 )* (1-5*0,1 ) -5 * ( -1 * 4 + 1 ) *( 1 + 1*4 )=
4* 1,5 * 0,5 - 5 * (-3 ) * 5 = 3 + 15*3 = 3+45 = 48
4* ( 5*0,1 + 1 )* (1-5*0,1 ) -5 * ( -1 * 4 + 1 ) *( 1 + 1*4 )=
4* 1,5 * 0,5 - 5 * (-3 ) * 5 = 3 + 15*3 = 3+45 = 48
= 4 * (1 - 25y²) -5 * (1 - 16x²) = 4 - 100y² - 5 + 80x² =
= -1 - 100y² + 80x²
dla x = -1 y= 0,1
-1 - 100* (0,1)² + 80* (-1)² = -1 - 100*0.01 + 80 =
= -1 - 1 + 80 = 80 - 2 = 78
= -1 - 100y² + 80x²
dla x = -1 y= 0,1
-1 - 100* (0,1)² + 80* (-1)² = -1 - 100*0.01 + 80 =
= -1 - 1 + 80 = 80 - 2 = 78